Histamine production by Klebsiella pneumoniae and an incident of scombroid fish poisoning. - Taylor, S L (1979)
A histamine-producing strain of Klebsiella pneumoniae was isolated from a sample of tuna sashimi implicated in an outbreak of scombroid fish poisoning. None of the other nine gram-negative bacterial strains isolated from the tuna sashimi was capable of equivalent histamine production. Bacterial histamine production was monitored in a tuna fish infusion broth (TFIB), and the implicated K. pneumoniae was capable of producing 442 mg of histamine per 100 g of tuna in TFIB in 7 h under controlled incubation conditions. Only 12 of 50 other K. pneumoniae strains, representing 5 distinct biochemical types, which had been originally isolated from foods, were able to produce such levels of histamine in TFIB. No correlation was found between histamine production and other biochemical characteristics or antibiotic resistance. Of the 12 histamine-producing strains, 11 belonged to type 2, which is characterized as indole negative with positive reactions in the urea and Voges-Proskauer tests. However, only 50% of the type 2 strains examined produced high levels of histamine in TFIB. Additionally, the implicated K. pneumoniae strain and one other strain belonged to type 1, which is characterized by positive reactions in the indole, urea, and Voges-Proskauer tests.